The men with broken faces : gueules cassées of the First World War - Gehrhardt, Marjorie (Cultural history and literary imagination ;, 2015)
"Perhaps the ultimate victims of the Great War, facially wounded servicemen became walking reminders of the conflict and their experiences reveal the impact of the war not only on the combatants but also on European societies at large. This book explores for the first time the individual and collective significance of First World War facially disfigured combatants, with a special focus on France, Germany and Great Britain. The analysis undertaken in this book uncovers how the wounded perceived and presented themselves and were perceived and represented by others. Artistic and literary representations are considered, along with initiatives on behalf of hospitals, the government and their fellow countrymen. With an interdisciplinary and comparative approach, this study illuminates our understanding of how the combatant and the onlooker made sense of the experience and the memory of the war"--Provided by publisher.